What are the Expert's Views on the Direction of the Malaysian Palm Oil Industry and Factors Shaping its Profitability? - Teoh, Ai Boon (2010)
Palm Oil accounts for 28% and 56% of the global oils and fats production and trade respectively. Both Malaysia and Indonesia together are the world largest producers and exporters of palm oil with 85% and 91% share of world palm oil production and export respectively1 (see Appendix 1). The paper outlines the increasingly dominant role that palm oil plays in world oils and fats supply and demand equation. The ascent of palm oil as powerhouse in the global oils and fats market has been achieved by leveraging upon the techno-economic advantages of palm oil vis-à-vis competing oils as well as positive developments arising from consumer concerns on health, environment, and food and energy security. In efforts to maintain continued market growth, the future direction of the industry and factors shaping its sustainable profitability will be examined.